1985
DOI: 10.1007/bf02032316
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of proteoglycans, elastase, collagenase and protein in synovial fluid in inflammatory and degenerative arthropathies

Abstract: The number of leucocytes and the concentrations of protein, proteoglycans (PG), elastase a1 proteinase inhibitor complexes (E-alpha 1 Pi) and collagenolytic activity were measured in the synovial fluid (SF) of 15 patients with rheumatoid arthritis (RA) and 18 with osteoarthritis (OA). The mean levels of protein, E-alpha 1 Pi and collagenase and the number of leucocytes were higher in RA than in OA SF. However, the mean level of PG was higher of OA SF than in RA. In the latter, they were principally in the form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

1987
1987
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Additionally, inflammation of the synovium may also cause an influx of such cells äs macrophages which may also be responsible for the secretion of cathepsin B and other proteases into the synovial fluid. It is known, for example, that collagenase levels are elevated in diseased, particular inflammatory, conditions again suggesting that proteolytic degradation may play an important role in arthritic disease (32). Cathepsin B has also been identified by other workers in rheumatoid synovial fluid (31) and also in synovial fluid with various forms of arthritis (33), using immunochemical methods.…”
Section: Resultsmentioning
confidence: 94%
“…Additionally, inflammation of the synovium may also cause an influx of such cells äs macrophages which may also be responsible for the secretion of cathepsin B and other proteases into the synovial fluid. It is known, for example, that collagenase levels are elevated in diseased, particular inflammatory, conditions again suggesting that proteolytic degradation may play an important role in arthritic disease (32). Cathepsin B has also been identified by other workers in rheumatoid synovial fluid (31) and also in synovial fluid with various forms of arthritis (33), using immunochemical methods.…”
Section: Resultsmentioning
confidence: 94%
“…Those methods lack the specificity of our assay, and meaningful comparisons of results are therefore precluded. However, Gysen and coworkers (22), using a radioimmunoassay to study synovial fluid proteoglycan concentrations in RA patients, found that the mean concentration was 12.6 pg/ml (n = 15). That result is consistent with our findings.…”
Section: Manifestations Of the Arthritismentioning
confidence: 99%
“…Synovial fluid is composed of hyaluronan and D-N-acetylglucosamine, as well as many enzymes [1517], among them matrix metallopeptidase 1 (MMP-1), elastase and plasmin, found in the synovial fluid at varying concentrations [1820]. These three enzymes are hypothesized to affect the healing of intra-articular injuries [2128].…”
Section: Introductionmentioning
confidence: 99%